Sosialisasi Penguatan Kelembagaan Desa (PKK) Di Era Disrupsi Di Mekarjadi Kecamatan Sadananya - Ayu Yuliani; Destian Rahmatul Azis; Hasna Nurfaidah; Irfan Nursetiawan; Rika Sri Wahyuni (Nusantara Mengabdi Kepada Negeri, 2024)
Village Institutions in Village Government have their respective functions and authorities. Family Welfare Empowerment (PKK) as one of the Village institutions has a function as a bridging forum in order to empower women to participate in Indonesia's welfare development. Like other village institutions, Family Welfare Empowerment (PKK) in Mekajadi Village, Sadananaya District, Ciamis Regency, generally has the same function. Therefore, this service activity aims to provide increased understanding regarding the function of the village institution itself, namely the PKK, in the current era of disruption. The method used in this activity is carried out by providing awareness or increasing understanding about the PKK as one of the Village institutions. The results of this activity show that there is still a need to increase human resources to improve quality in the current era of disruption